Gambaran Penggunaan Alat Pelindung Diri oleh Perawat di Ruang Perawatan Rumah Sakit - Devi Nurmalia; Sarah Ulliya; Linawati Neny; Agnes Agustina Hartanty (Holistic Nursing and Health Science, 2019)
Introduction: Health Care Associated Infection (HAIs) is a major problem faced throughout the world and this incident continues to increase. The use of Personal Protective Equipment (PPE) of nurses is inadequate. Previous studies have not yet described how the suitability of PPE use with the actions taken by nurses. Therefore, in this study will be described how the use of PPE by nurses. The study aimed to identify nurse compliance in using PPE.Methods: This was a descriptive analytic and observation method for data collection. The sample in this study was an action carried out by nurses, in this case the nurse was observed to suit the use of PPE with Standard Operating Procedure (SPO) in the hospital. The sampling technique used was accidental sampling towards 67 actions of PPE using observation sheet according to hospital SPO. Data is processed univariately and presented in the form of frequency distribution.Results: The result showed that, PPE most frequently used in general ward that is gloves, mask, and also apron. The results showed that as many as 54,39% of actions taken by nurses were inappropriate in the use of glove. The use of masks and apron among the nurses is almost entirely correct, only 1 mask error was found.Conclusion: PPI through Infection Prevention Control Nurse (IPCN) should provide socialization and information on the use of PPE in accordance with hospital standard operational procedure. IPCN is expected to be an appropriate role model in the use of PPE, while the head nurse provides motivation and spirit to the nurses to be more compliant in the procedure when using gloves.